2014
DOI: 10.1038/bcj.2014.12
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated WNT signaling in childhood T-cell acute lymphoblastic leukemia

Abstract: WNT signaling has been implicated in the regulation of hematopoietic stem cells and plays an important role during T-cell development in thymus. Here we investigated WNT pathway activation in childhood T-cell acute lymphoblastic leukemia (T-ALL) patients. To evaluate the potential role of WNT signaling in T-cell leukomogenesis, we performed expression analysis of key components of WNT pathway. More than 85% of the childhood T-ALL patients showed upregulated β-catenin expression at the protein level compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 43 publications
5
71
0
Order By: Relevance
“…In adult human mesenchymal stem cells from bone marrow stoma, high levels of DKK1 allow the cells to reenter the cell cycle by inhibiting the canonical WNT pathway (19). In our previous study, deregulated WNT/β-catenin signaling was shown as a novel oncogenic event in childhood T-ALL (20), whereas this is not the case for B-ALL patients (unpublished data). Here, DKK1 expression was not significant in T-ALL, supporting our previous findings due to the canonical WNT inhibitor role of DKK1.…”
Section: Discussionmentioning
confidence: 94%
“…In adult human mesenchymal stem cells from bone marrow stoma, high levels of DKK1 allow the cells to reenter the cell cycle by inhibiting the canonical WNT pathway (19). In our previous study, deregulated WNT/β-catenin signaling was shown as a novel oncogenic event in childhood T-ALL (20), whereas this is not the case for B-ALL patients (unpublished data). Here, DKK1 expression was not significant in T-ALL, supporting our previous findings due to the canonical WNT inhibitor role of DKK1.…”
Section: Discussionmentioning
confidence: 94%
“…[36][37][38] Here, we employed the small molecule tankyrase inhibitor XAV-939 that enhances b-catenin turnover by stabilizing AXIN. 39 XAV-939 showed efficacy against human T-ALL cell lines in vitro in a dose-dependent manner and modest synergy in combination with a g-secretase inhibitor that blocks Notch signaling ( Figure 6B-C).…”
Section: Antagonizing Wnt Signaling In Human T-allmentioning
confidence: 99%
“…Constitutive activation of NOTCH and β-catenin-mediated WNT signaling pathways are two of the most important and common alternations found in T-ALL [35, 36], and c-Myc is the direct transcriptional target of both pathways. In this study, we showed that DEX could inhibit both c-Myc and β-catenin expressions in GC- sensitive CEM-C7 cells, but not in GC-resistant CEM-C1 cells.…”
Section: Discussionmentioning
confidence: 99%